The Acoustic and Peceptual Effects of Series and Parallel Processing. (28th September 2009) - Anderson Anderson, Melinda C. Melinda C.; Arehart Arehart, Kathryn H. Kathryn H.; Kates Kates, James M. James M.
Abstract : Temporal envelope (TE) cues provide a great deal of speech information. This paper explores how spectral subtraction and dynamic-range compression gain modifications affect TE fluctuations for parallel and series configurations. In parallel processing, algorithms compute gains based on the same input signal, and the gains in dB are summed. In series processing, output from the first algorithm forms the input to the second algorithm. Acoustic measurements show that the parallel arrangement produces more gain fluctuations, introducing more changes to the TE than the series configurations. Intelligibility tests for normal-hearing (NH) and hearing-impaired (HI) listeners show (1) parallel processing gives significantly poorer speech understanding than an unprocessed (UNP) signal and the series arrangement and (2) series processing and UNP yield similar results. Speech quality tests show that UNP is preferred to both parallel and series arrangements, although spectral subtraction is the most preferred. No significant differences exist in sound quality between the series and parallel arrangements, or between the NH group and the HI group. These results indicate that gain modifications affect intelligibility and sound quality differently. Listeners appear to have a higher tolerance for gain modifications with regard to intelligibility, while judgments for sound quality appear to be more affected by smaller amounts of gain modification.